1992
DOI: 10.1161/01.atv.12.9.1008
|View full text |Cite
|
Sign up to set email alerts
|

Role of the extracellular matrix in age-related modifications of the rat aorta. Ultrastructural, morphometric, and enzymatic evaluations.

Abstract: Connective tissues such as blood vessels are known to be greatly affected by age because of impaired functional properties and increased susceptibility to diseases. With the aim of providing further information on the role of the extracellular matrix in age-related modifications, we investigated the aorta in the rat model from birth to senescence by means of morphological and morphometric observations and by evaluation of lysyl oxidase activity. Results focused on the dramatic vascular rearrangements due to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…There are two types of collagen crosslinking: crosslinks mediated by lysyl oxidase and those derived from glycation. The decrease in lysyl oxidase-mediated crosslinks in interstitial collagen is in agreement with the finding that lysyl oxidase activity decreases with age (Sanada et al 1978;Fornieri et al 1992). These data suggest that the AGEmediated collagen crosslinks indicated by increased collagen fluorescence in our study are the main cause of the structural alteration in GBM that occurs with aging.…”
Section: Discussionsupporting
confidence: 92%
“…There are two types of collagen crosslinking: crosslinks mediated by lysyl oxidase and those derived from glycation. The decrease in lysyl oxidase-mediated crosslinks in interstitial collagen is in agreement with the finding that lysyl oxidase activity decreases with age (Sanada et al 1978;Fornieri et al 1992). These data suggest that the AGEmediated collagen crosslinks indicated by increased collagen fluorescence in our study are the main cause of the structural alteration in GBM that occurs with aging.…”
Section: Discussionsupporting
confidence: 92%
“…High blood pressure exacerbates the situation by forcing the artery to work in a less compliant range. 32,34,35 We found that, unlike the curly shaped elastin fibers in aortas from aged WKY rats, elastin fibers in the aorta of SHRs were straight and remained unchanged after relaxin therapy. Relaxin therapy significantly reduced collagen content, estimated either as total content per centimeter segment or percentage of dry weight but without change in elastin level, resulting in a significant increase in the elastin:collagen ratio and arterial compliance.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies revealed that arterial collagen content increased progressively with aging and became more insoluble and crosslinked. 30,32 In sharp contrast, vascular elastin synthesis is active in newborn and young rats, and becomes quiescent in aged animals resulting a reduced elastin:collagen ratio. 33 Elastin is more extensible, but collagen fibers are very rigid.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 Studies from our laboratory and others have shown that diffuse intimal thickening with aging is characterized by accumulation of fibronectin, collagen, and vascular smooth muscle cells (VSMCs), with an increase in matrix metalloproteinase (MMP)-2 and angiotensin II (Ang II) expression. [7][8][9][10][11] In addition, the expression of aortic intracellular adhesion molecule and transforming growth factor-␤1 markedly increases with age, and these molecules localize to MMP-2-staining positive areas. 12 Arterial aging is also characterized by an increase in NAD(P)H oxidase activity and reactive oxygen species production and a reduction in nitric oxide (NO) bioavailability.…”
mentioning
confidence: 99%